Global increase in the endemism of birds from north to south - D. Matthias Dehling; Steven L. Chown (Nature Communications)
Abstract Endemism is a highly valuable metric for conservation because it identifies areas with irreplaceable species, ecological functions, or evolutionary lineages. Global analyses of endemism currently fail to identify the most irreplaceable areas because the commonly used endemism metrics are correlated with richness, and entire regions, especially low-richness areas in the southern hemisphere, are regularly excluded. Global patterns of endemism are therefore still insufficiently known. Here, using metrics representing irreplaceability, we unveil global patterns of avian taxonomic, functional, and phylogenetic endemism that show striking differences between hemispheres. Across all facets of diversity, endemism decreases poleward in the northern hemisphere but increases poleward in the southern hemisphere, resulting in a global north-south increase in endemism. The pattern appears to be driven by smaller and increasingly discontinuous landmasses towards the south which lead to smaller ranges and reduced overlap in community composition, as well as to global peaks of diversity relative to available area in the southern hemisphere. Our findings suggest that there are key areas of irreplaceability that might be missed if analyses are focused on species richness and omit species-poor regions. Highly endemic southern-hemisphere communities might be especially vulnerable to the climate crisis because discontinuous landmasses impede range shifts.